The Community Caring Collaborative: Case Study of a Grassroots Collaboration to Create a System of Care for At-risk Infants, Young Children, and Their Families in Washington County, Maine - Withers, Marjorie (Maine Policy Review, 2009)
Marjorie Withers presents a case study of rural Washington County, Maine, where community-agency partnerships are increasing services for community members and their children affected by exposure to drugs, alcohol, and other risk factors. The Community Caring Collaborative (CCC) is an effective model in part because of its structure. But most important, according to Withers, is the creation of hope and new energy in an area of the state characterized by longstanding feelings of hopelessness and powerlessness.